성인여성들의 16주간 유산소 운동이 성호르몬 변화에 미치는 영향 - 임동현; Lim Dong-hyun; 전유정; Jeon Yoo-jeong (국제문화예술, 2023)
연구목적: 본 연구는 T시에 거주하는 건강하고 활동적인 성인여성으로 실험군 15명과 통제군 9명 총 24명을 대상으로 16주간 유산소 운동을 시행함에 따라 대표적인 여성호르몬인 에스트로겐, 에스트라디올, 프로게스테론, 난포자극호르몬의 변화에 어떻게 영향을 줄 수 있는지의 궁금함을 해소하고 여성들의 건강과 컨디션 관리에 운동이 끼칠 수 있는 영향을 알아보기 위한 목적이 있다. 연구방법: 실험군은 16주 동안 주 4회, 60분 동안 유산소성 운동으로서 댄스 스포츠 운동을 실시하였으며, 10분간의 준비운동을 실시한 후 댄스 운동 프로그램에 맞추어 60-70%HRmax로 40분의 본 운동을 실시하고, 본 운동이 끝난 후 10분간의 정리운동을 실시하였다. 연구 기간 동안 피험자들은 8주 간격으로 여성호르몬 검사를 받았다. 본 연구에서는 각 실험 기간 동안 각 집단을 살펴보는 반복 측정을 통해 요인을 이중 분석한 후 SNK(student newman-keuls) 방법을 통해 비교 분석하였다. 연구결과: 연구의 결과로서 여성의 대표적인 호르몬인 에스트로겐(Estrogen)은 실험 전·중·후의 평균치의 차이에 대한 검증을 위하여 반복측정에 의한 이원변량분석을 실시한 결과 그룹간에 유의한 차이(F=7.19, p<.01)를 나타내어 SNK(student newman-keuls)에 의한 사후검증을 실시한 결과 실험군이 통제군보다 유의하게 높게 나타났으며 운동처치기간이 길어짐에 따라 점차 증가하는 결과를 나타내었다. 에스트라디올(Estradiol)은 실험 16주 후에 9.78% 증가하였으며, 프로게스테론(Progesterone)은 실험 16주 후에 11.58% 증가하였고 난포 자극 호르몬(Follicle stimulating hormone ; FSH)은 16주 후에 15.43% 증가하였으나 처지기간, 그룹과 처지기간의 상호작용에 있어서 유의한 차이가 없는 것으로 나타났다. 결론: 본 연구는 16주간의 유산소성 운동이 성인 여성의 호르몬 작용에 긍정적인 영향을 미친다는 것을 나타냈으며 호르몬으로 인하여 건강상의 영향을 많이 받는 여성들의 성 호르몬 수치를 조절하고 신체의 컨디션 개선과 여성들이 고통 받고 있는 질환을 개선할 수 있는 긍정적인 효과를 가져올 것이라고 생각되고 향후에는 각 개인의 체력 상태나 생활습관의 차이점을 고려한 여성들의 운동방법에 대한 추가적인 연구가 필요할 것이라고 사료된다. Purpose: In this study, a total of 24 healthy and active adult women, 15 in the experimental group and 9 in the control group, residing in T city, were subjected to aerobic exercise for 4 months, and the representative female hormones estrogen, estradiol, progesterone, The purpose of this study is to answer questions about how it can affect changes in follicle-stimulating hormone and to find out the impact exercise can have on women’s health and condition management. Methods: The experimental group performed dance sports exercise as aerobic exercise for 60 minutes 4 times a week for 16 weeks. In this study, factors were double-analyzed through repeated measures looking at each group during each experiment period, and then comparatively analyzed through the SNK(student newman-keuls) method. Result: As a result of the study, in order to verify the difference in the average value of estrogen, a representative female hormone, before, during, and after the experiment, a two-way ANOVA was conducted by repeated measurements. As a result, there was a significant difference between the groups (F=7.19, p< .01), and as a result of post-test by SNK (student newman-keuls), the experimental group showed significantly higher than the control group, and the result showed a gradual increase as the exercise treatment period became longer. Estradiol increased by 9.78% after 16 weeks of the experiment, progesterone increased by 11.58% after 16 weeks of the experiment, and follicle stimulating hormone (FSH) increased by 15.43% after 16 weeks of the experiment. There was no significant difference in the interaction between and sagging. Conclusion: In this study, 16 weeks of aerobic exercise had a positive effect on adult women’s hormones and it controlled the levels of sex hormones in women whose health was greatly affected by hormones, and improved physical condition and women. It is thought that this will bring about a positive effect that can improve the suffering disease, and in the future, additional research on women’s exercise methods will be needed considering the differences in each individual’s physical condition and lifestyle.